SEEDS GERMINATION OF SALAD ROCKET UNDER DIFFERENT TEMPERATURES - STEINER, Fábio; JUNIOR, Artur Soares PINTO; DRANSKI, João Alexandre Lopes; ZOZ, Tiago; RHEINHEIMER, Ana Raquel (Scientia Agraria, 2010)
The temperature influence dramatically the seed germination and seedling emergence of crops. An experiment was conducted at the Laboratory of Technology in Seeds and Seedlings of UNIOESTE, Campus of Marechal Cândido Rondon/PR with the objective to evaluate the adverse effect of temperature on the germination of salad rocket seed. Were used seeds of two species, a cultivar of the specie Diplotaxis tenuifolia (‘Savage Salad Rocket’) and three cultivars of the species Eruca sativa (‘Cultivated’, ‘Cultivated – Giant Wide Leaf’ and ‘Apreciatta – Wide Leaf’). The seeds were evaluated for to moisture degree, to first count of germination, to length of the primary root, to germination at 10, 20 and 35 ºC, to seedling emergence. The experimental design used was the entirely randomized in schedule factorial 4 x 3 + 1 with four replications, composed of four cultivars and three temperatures and an additional treatment with emergency in substrate under conditions of greenhouse. The cultivars of the specie Eruca sativa (‘Cultivated’, ‘Cultivated – Giant Wide Leaf’ and ‘Apreciatta – Wide Leaf’) possess satisfactory germination (more than 94%) at temperatures ranging from 10 to 35 ºC. however seeds of specie Diplotaxis tenuifolia (‘Savage Salad Rocket’) germinate better (77%) in temperatures around 20 ºC, and temperature of 10 ºC is not suitable for germination of this specie, by providing less than 10% germination.